EVALUATION OF THE WEST JAVA KARATE TEAM TRAINING PROGRAM AT PON XXI ACEH AND NORTH SUMATERA IN 2024 - Sandy Firmansyah, Sandy Firmansyah; akhmad Sobarna, akhmad Sobarna; Muchamad Ishak, Muchamad Ishak; Irpan, Irpan; Erik Nurkamdani, Erik Nurkamdani (UNIB Press, 2025)
This study aims to evaluate the effectiveness of the West Java Karate team training program in preparation for the XXI North Sumatra-Aceh National Sports Week (PON) 2024. The evaluation was conducted using the CIPP (Context, Input, Process, Product) model which includes an analysis of the objectives, resources, implementation process, and final results of the training program. The research method used is descriptive qualitative with data collection techniques through observation, interviews, documentation studies, and questionnaires. The population in this study were all members of the West Java Karate team who participated in the XXI North Sumatra-Aceh PON 2024, consisting of 23 people, including athletes and coaches. The sampling technique used was total sampling, where the entire population was used as a research sample to obtain more accurate and representative data. The results of the study showed that the training program had a strong foundation in terms of objectives, regulations, and athlete needs. The input dimension shows that support for human resources, facilities and infrastructure, and funding is quite adequate, although there is still room for improvement. From the process aspect, the program has been running effectively with a balance between training and education for athletes, as well as attention to their welfare. The product dimension evaluation showed that the West Java Karate team managed to win 2 gold medals, 3 silver medals, and 2 bronze medals, reflecting the success of the training program in improving athlete performance. Although the program has been running well, this study recommends improvements in aspects of training facilities, sports science-based coaching methods, athlete welfare, and continuous evaluation and monitoring. The implementation of these recommendations is expected to increase the effectiveness of the training program and support the achievement of more optimal achievements for the West Java Karate team in future competitions